Energy exchange between athlete and vaulting pole: Effects on pole vault performanmce - Schade, F. (Deutsche Sporthochschule Köln, 2013)
Abstract The presented thesis provided a deeper insight into issues of interaction between athlete, vaulting pole, and ground in the pole vault. The results confirmed that the concept of energy storage and return is effectively applicable to the pole vault event and can have decisive impact on optimizing pole vault technique. The main findings and conclusions of the thesis are presented in two parts. The first part (I) contains the examination of methodological aspects of the concept of energy storage and return in the pole vault to proof the applicability of the concept. The second part (II) deals with the application of aspects of the concept of energy storage and return to practical relevant questions of the pole vault: (I) Differences between two and three dimensionally calculated mechanical energy of the athlete in the pole vault were statistical significant (p<0.05). They are an expression of the movements that take place in the plane perpendicular to the main plane of movement. Differences between centre-of-mass energy and total body energy of the vaulter were statistically significant (p<0.05). They are the result of segmental movements that occur relatively to the centre-of-mass. These different approaches of calculating the athlete`s mechanical energy, with this movements apart from the main plane of movement and segmental movements relatively to the centre-of-mass, do not relevantly influence energy parameter values used for the calculation of the criteria of energy exchange in the pole vault developed by Arampatzis et. al. (1997, 2004). The findings indicate that, concerning the economy of data acquisition, for the calculation of the criteria a two-dimensional database allows to calculate adequately accurate results, the same as the calculation of the centre-of-mass energy compared to the calculation of the total mechanical body energy does. Kinematic, dynamometric and derived mechanical energy parameters in the pole vault were reproducible. On the basis of nearly constant initial mechanical conditions of a vault (constant external conditions like pole stiffness, grip height, wind conditions, and a high reproducibility of the initial mechanical energy of the vaulter and the take-off distance) the athletes achieved intraindividual similar jump performances achieved by reproducible interactions with the elastic vaulting pole. It can be concluded that the reproducibility of parameters and criteria used in the energy exchange concept in the pole vault (Arampatzis et al. 1997, 2004) is sufficient to analyze one completed vault to determine the impact of changes in movement pattern on the energy exchange between vaulter and pole in different phases of the vault. (II) The comparison of elite male and female vaulters in terms of the athlete`s mechanical energy development and mechanical energy parameters during the pole vault revealed a similar development of the vaulters energy parameters for men and women, but significantly higher values (p<0.05) in the initial energy, vaulter`s energy at maximum pole bend and final energy for the men. The energy gain of the complete vault was similar for men and women. The comparison of elite male and female vaulters in terms of the development of the athlete`s angular momentum around the transversal axis through the centre-of-mass during the vault revealed significantly (p<0.05) higher values for the female vaulters during initial pole bend and bar clearance. Even though the energy gain of the complete vault is similar for men and women, the differences in angular momentum reveal deficits in movement behavior of the female vaulters. The higher angular momentum during initial pole bending hints at a passive upward swing rather than at an active pole bending action. The same does a significantly (p<0.05) lower maximum pole bending by the female vaulters. It can be concluded that the pole vaulting technique of elite female vaulters is not a projection of the technique of male vaulters at a lower jump height level, but rather a different way of vaulting and interacting with the elastic pole that leaves room for further improvement. The examination of the effect of an earlier pole plant during the stance phase of the jump on the energy level of the vaulter/pole system at take-off during a special pole vault take-off exercise (Jagodin) revealed that a variation of the point in time influences the interactions between vaulter, pole and ground. But it does not influence the energy level of the vaulter/pole system and is therefore not related to the performance of the jump and plant complex in Jagodins. Although an earlier pole plant increases the loss of energy by the vaulter during the take-off, this is counterbalanced by an increase in the energy stored in the pole at take-off. The Jagodins performed in the current study differ slightly from competition vaults, whereas most of the differences are a result of the lower initial energy of the Jagodins. The lower initial energy of the Jagodins should not change the general effect of the timing of the pole plant on performance criteria, so similar interactions can be expected in complete vaulting, too. Zusammenfassung Die vorliegende Arbeit liefert neue Erkenntnisse zur Interaktion zwischen Athlet, Sprungstab und Boden im Stabhochsprung. Die Ergebnisse zeigen, dass das Konzept von Energiespeicherung und -rückgabe sinnvoll im Stabhochsprung angewendet werden kann und das es einen entscheidenden Einfluss auf die individuelle Optimierung der Stabhochsprungtechnik haben kann. Die Ergebnisse und Schlussfolgerungen werden in zwei Abschnitten dargestellt. Der erste Abschnitt (1) beinhaltete methodologische Aspekte des Konzepts von Energiespeicherung und -rückgabe im Stabhochsprung, um grundsätzlich dessen Anwendbarkeit zu überprüfen. Der zweite Abschnitt (2) befasst sich mit der Anwendung von Aspekten des Konzepts von Energiespeicherung und -rückgabe auf praktisch relevante Fragestellungen im Stabhochsprung. (1) Die zwei und drei dimensional berechnete mechanische Energie des Athleten im Stabhochsprung unterscheidet sich signifikant (p<0,05). Die Unterschiede sind das Resultat von Bewegungen außerhalb der Hauptbewegungsebene. Die Unterschiede zwischen KSP Energie und Gesamtenergie des Körpers sind ebenfalls signifikant (p<0,05) und sind mit Körpersegmentbewegungen, welche relativ zum KSP auftreten, zu erklären. Diese unterschiedlichen Berechnungsverfahren zur Bestimmung der mechanischen Energie des Athleten und damit Bewegungen außerhalb der Hauptbewegungsebene und relative Segmentbewegungen um den KSP haben allerdings keinen relevanten Einfluss auf Energieparameter, welche zur Berechnung der Kriterien des Energieaustauschs nach Arampatzis et al. (1997, 2004) verwendet werden. Diese Ergebnisse legen den Schluss nahe, dass eine zweidimensionale Datenbasis und eine KSP bezogene Energieberechnung ausreichend genaue Ergebnisse für die Berechnung der Kriterien liefert. Das bedeutet, dass die Datenerfassung für die Anwendung des Energiekonzepts im Stabhochsprung deutlich ökonomisiert werden kann. Sowohl kinematische und dynamische Parameter, als auch abgeleitete Parameter der mechanischen Energie sind im Stabhochsprung reproduzierbar. Bei nahezu konstanten Anfangsbedingungen des Sprungs (konstante externe Bedingungen wie Stabhärte, Griffhöhe, Windverhältnisse und reproduzierbare Anfangsenergie des Springers und Absprungweite) zeigen Athleten intraindividuell ähnliche Sprungleistungen, welche durch reproduzierbare Interaktionen mit dem elastischen Sprungstab zustande kommen. Wir können schlussfolgern, dass die Reproduzierbarkeit der Parameter und Kriterien des Energiekonzepts im Stabhochsprung (Arampatzis et al. 1997, 2004) ausreichend ist, um auf der Grundlage eines analysierten kompletten Versuchs der Einfluss von Veränderungen des Bewegungsverhaltens auf den Energieaustausch zwischen Athlet und Sprungstab in verschiedenen Phasen des Sprunges zu bestimmen. (II) Ein Vergleich von Weltklasse Stabhochspringerinnen und Stabhochspringern in Bezug auf Parameter der mechanischen Energie zeigt ähnliche Energieverläufe. Wobei die Anfangsenergie, die Athletenenergie im Moment der maximalen Stabbiegung und die Endenergie bei den männlichen Springern signifikant höher ist (p<0,05). Der Energiegewinn über den gesamten Sprung ist jedoch für Männer und Frauen gleich. Der Drehimpuls um die Transversalachse durch den Körperschwerpunkt zeigt im Vergleich signifikant höhere Werte (p<0,05) für die Stabhochspringerinnen in der Phase der initialen Stabbiegung und bei der Lattenüberquerung. Obwohl es keine Unterschiede im Energie Gewinn gibt, deuten die Unterschiede im Drehimpuls auf Defizite in der Bewegungstechnik der Frauen hin. Der höhere Drehimpuls unmittelbar nach Einstich des Stabs weist darauf hin, dass Stabhochspringerinnen eher passiv nach oben pendeln als den Stab aktiv zu biegen. Dies wird durch die signifikant geringere maximale Stabbiegung der Frauen unterstützt (p<0,05). Es kann gefolgert werden, dass die Stabhochsprung Technik von Frauen auf Weltklasse Niveau keine Projektion der Stabhochsprung Technik von Weltklasse Männern ist, sonder das Frauen vielmehr eine andere Weg der Interaktion mit dem elastischen Sprungstab zeigen, welcher Spielraum für weitere Verbesserungen lässt. Eine Analyse des Einflusses von Einstichzeitpunkt des Stabs während der Stützphase des Absprunges bei einer Einstich/Absprung Übung (Jagodin) auf das Energieniveau des Springer/Stab Systems zeigt, das eine Veränderung des Einstichzeitpunkts zu einer veränderten Interaktion zwischen Athlet, Sprungstab und Boden führt. Sie führt aber nicht zu einer Veränderung des Energie Niveaus der Springer/Stab Systems bei Boden verlassen und ist damit nicht unmittelbar leistungsrelevant für den Einstich/Absprung Komplex bei Jagodins. Obwohl ein früherer Einstich den Energieverlust des Athleten während des Einstich/Absprung Komplexes vergrößert, bleibt die Energieänderung des Gesamtsystems Springer/Stab unbeeinflusst, da diese Abnahme durch die Energiezunahme der Stabenergie kompensiert wird. Die in dieser Studie untersuchten Jagodins unterscheiden sich gering von Wettkampfsprüngen, wobei der größte Unterschied in der niedrigeren Anfangsenergie bei den Jagodins liegt. Dies sollte aber nicht grundsätzlich den Effekt des Einstich Timings auf Leistungskriterien beeinflussen. Somit sind ähnliche Effekte auf die Interaktion zwischen Springer, Stab und Boden auch bei kompletten Sprüngen zu erwarten.